Health Shocks and the Hazard Rate of Early Retirement in the ECHP - Ronald Hagan; Andrew M. Jones; Nigel Rice (Swiss Journal of Economics and Statistics, 2008)
In this paper we use discrete-time proportional hazard models with internationally comparable longitudinal data from the full eight waves of the European Community Household Panel (ECHP) to study the relationship between retirement, health levels and health shocks in nine European countries. The results show a consistency of effect with only small variation in magnitude both for latent health stock variables as well as the subjective SAH measures. This is compatible with previous findings that declining health is associated with an increased probability of retirement. Additionally a three-level graduated acute health shock variable was created, that shows evidence of a gradient in the effect.
Keywords: H55; I12; J26; 330; Retirement; Health; ECHP; European Union